What Elephant? Pedagogical Approaches to Addressing Stigma Toward Mental Disorders in Undergraduate Public Health Education. (September 2021) - Mezuk, Briana; Needham, Belinda; Joiner, Kevin; Watkins, Daphne; Stoddard, Sarah; Burgard, Sarah; Link, Bruce
In the past decade, the number of undergraduate public health programs has increased exponentially. This growth provides a unique opportunity to explore concepts and issues relevant to understanding the determinants of health at a population level using new pedagogical approaches. One of these issues is stigma toward mental disorders. Stigma is a concept that refers to a feature or characteristic that reduces, devalues, and disempowers a person. Given the prevalence of mental and substance use disorders among college students, undergraduate education is an important setting for attempting to address stigmatizing attitudes both for society at large and for faculty, staff, and students, including those experiencing mental health problems. This article describes an effort to develop an undergraduate course in public mental health that explicitly addresses the ways stigma shapes student understanding of this topic and discusses lessons learned from this experience.